Teaching criminology through interview-based assignments - Mark Israel (Legal Education Review)
Over the last three years, I have continued to change the way in which I taught criminology. I have used an assessed interview-based assignment to try to support active learning. Students have been encouraged to develop an understanding of the tools and resources available to them, apply this understanding to a specific area, and be self-motivated and reflexive.